The Effects of Husbands' Alcohol Consumption and Women's Empowerment on Intimate Partner Violence in India. Issue 13 (July 2022) - Parekh, Aneree; Tagat, Anirudh; Kapoor, Hansika; Nadkarni, Abhijit
The influence of husband's alcohol consumption and that of women's empowerment has been largely studied separately in relation to the intimate partner violence (IPV) faced by women, which has hindered a nuanced understanding of gender-based violence in India. This study aimed to understand how husbands' alcohol consumption shapes the relationship between women's empowerment and violence among Indian couples. Data from the 2015–16 National Family Health Survey (NFHS) were used in this study. A composite women's empowerment index was constructed and its association with husbands' drunkenness and odds of facing emotional, physical, severe, and sexual violence was examined. This study found that compared to women whose husbands were never drunk, those whose husbands were sometimes or often drunk had significantly higher odds of experiencing physical, emotional, and sexual violence. For all the types of IPV, an increase in the empowerment index was associated with a significant reduction in the odds of experiencing violence. However, increasing frequency of husband's drunkenness in combination with increasing scores on the empowerment index was associated with a significant increase in the odds of IPV, except sexual violence. Our findings highlight the nuances of IPV, situating the experiences of women in the social, cultural, and economic realities of Indian society.